Retiform hemangioendothelioma of the vulva: a case report - Hai-Jiao Wang; Zhi-Chen Ding; Xu Yan; Ying Yue (Clinical and Experimental Obstetrics & Gynecology)
Background: To report a rare case of retiform hemangioendothelioma (RH) originated from the vulva and review the relative references. Case: A 38-year-old woman was admitted to our hospital with a vulvar subcutaneous nodule (diameter about 2 cm) for 2 years. The clinical examination findings, laboratory test results, including complete blood count and liver function test results were normal. The B mode ultrasound revealed that a hypoechoic nodule with a clear boundary was observed on the right side of the vulva. The size was measured to be 23 mm × 8 mm. An expanded resection with the excision range extending 1 cm and the depth reaching the fascia was performed. The histologic examination revealed that the elongated, arborizing, thin-walled vessels were abundant on the tumor, the inner wall of the vessels was arranged with monolayer cells with uniform morphology. Local infiltration of lymphocyte has been found around the vessels. Immunohistochemical examinations showed that the endothelial cells were CD31, CD34 and friend leukemia virus integration 1 (Fli-1) positive, the smooth muscle actin (SMA) was scattered positive, further confirming the diagnosis of RH. The patient was followed up for 15 months, no local recurrence was found. Conclusions: Vulvar region is the rare affected region of RH, which is lack of characteristic findings in clinical examinations and laboratory tests. The pathology and immunohistochemistry are necessary for the diagnosis of vulvar RH. Local expanded resection of tumor may be an effective method for the treatment of early-stage RH to reduce the risk of local recurrence.